State of the Art in Designing Fish-Friendly Turbines: Concepts and Performance Indicators - Koukouvinis, Foivos (Phoevos); Anagnostopoulos, John (My University, 2023)
The expanding role of renewable energy sources in the electricity market share implies the increasing role of hydropower and the exploitation of unharnessed hydraulic potential, in the scope of sustainability and net zero emissions. Hydro-turbine design practices are expected to expand beyond achieving high efficiency goals, to multi-objective criteria ranging from efficient reversible operation to fish-friendly concepts. The present review paper outlines fundamental characteristics of hydropower, summarizing its potential impact toward aquatic life. Estimates of lethality for each damage mechanism are discussed, such as barotrauma, blunt impact and shearing, along with relevant advances in experimental techniques. Furthermore, numerical techniques are discussed, ranging from simple particle tracking to fully coupled six-degree-of-freedom tracking, which can be used to investigate candidate designs and their fish-friendly performance, presenting their advantages and disadvantages. Subsequently, a link to the individual damage mechanisms is established, to proposed holistic performance metrics, useful for providing estimates of fish-friendliness of a given hydropower installation. Finally, recent developments and design practices for fish-friendly turbine concepts are presented.
Keywords: experimental methods; fish injury assessment; fish-friendly hydropower; hydropower statistics; numerical methods; turbine design considerations